2001
DOI: 10.1136/gut.48.1.20
|View full text |Cite
|
Sign up to set email alerts
|

An exaggerated sensory component of the gastrocolonic response in patients with irritable bowel syndrome

Abstract: Background/aims-Visceral hypersensitivity is a feature of the irritable bowel syndrome (IBS). Postprandial symptoms are common in these patients. The eVects of nutrients on colonic perception in IBS are incompletely understood. Subjects-We studied 13 healthy subjects and 16 patients with IBS-eight had diarrhoea predominant (IBS-D) and eight constipation predominant (IBS-C) IBS. Methods-Colonic perception thresholds to balloon distension and viscerosomatic referral pattern were assessed before and after duodena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
135
2
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(155 citation statements)
references
References 46 publications
16
135
2
2
Order By: Relevance
“…Psychological factors not measured in this study, such as attribution, might be involved in the pathogenesis. The established changes in visceral sensory, perceptual and neuroendocrine responses seen in these subjects has been related to low-grade mucosal inflammation, IgG antibodies and other aspects of food allergy, infections, changes in the microflora, etc (Simren et al, 2001a;Barbara et al, 2002;Isolauri et al, 2004;Posserud et al, 2004). All these aspects of perceived food intolerance deserve further investigations.…”
Section: Discussionmentioning
confidence: 89%
“…Psychological factors not measured in this study, such as attribution, might be involved in the pathogenesis. The established changes in visceral sensory, perceptual and neuroendocrine responses seen in these subjects has been related to low-grade mucosal inflammation, IgG antibodies and other aspects of food allergy, infections, changes in the microflora, etc (Simren et al, 2001a;Barbara et al, 2002;Isolauri et al, 2004;Posserud et al, 2004). All these aspects of perceived food intolerance deserve further investigations.…”
Section: Discussionmentioning
confidence: 89%
“…Coates et al 26) confirmed that the 5-HT levels in the rectal mucosa in patients with IBS were significantly decreased compared with the control group. Simren et al 27) showed that 5-HT levels in the plasma of IBS-D patients were significantly lower than in healthy volunteers.…”
Section: Discussionmentioning
confidence: 99%
“…However, the [18] . IBS patients show a significantly reduced tolerance of balloon dilatation in the colon and rectum, displaying increased pain intensity [19] . Some scholars believe that this sensitivity may be related to an enhanced sensation in the peripheral or central nervous system, and it may also be related to abnormalities in the processing and integration of the incoming signal in the brain [20] .…”
Section: Discussionmentioning
confidence: 99%